Intellectual capital disclosure payback - Curado, Carla (2022)
Purpose – The purpose of this paper is to propose an integrated framework for intellectual capital disclosure. Design/methodology/approach – The measure, manage and report intellectual capital (MMRIC) methodology is a six-step process that will enable firms to more accurately describe their intangible assets. Findings – The proposed step-by-step process also complements the exploration-exploitation tension that is highlighted in the knowledge management literature. Research limitations/implications – This paper provides academic researchers with a comprehensive framework that can be utilized for future empirical studies related to intellectual capital disclosure. Practical implications – The MMRIC process is a very useful tool for practitioners in that it provides a sequential system that can be followed for intellectual capital disclosure. Social implications – Society at large benefits when corporate entities help to reduce risk and volatile market fluctuations by reducing information asymmetry with more comprehensive reporting. Originality/value – This paper provides an initial theoretical framework that has been developed by integrating the extant literature on intellectual capital disclosure..